Demonstration of the combination of slice imaging and Rydberg tagging for studies of photodissociation dynamics - Cruse, H; Softley, T (American Institute of Physics, 2004)
The slice-imaging variant of photofragment ion imaging is combined with Rydberg tagging. The photodissociation of NO2 at 355 nm is used as the test system and the NO fragments are Rydberg tagged by two-photon two-color excitation via the intermediate A²Σ+ state. Images obtained by this method are compared with ion images obtained in the same apparatus using the approach of Kitsopoulos and co-workers [Rev. Sci. Instrum. 72, 3848 (2001)]. Comparable resolution and angular distributions are obtained in the two cases. It is proposed that the method demonstrated here could provide a complementary approach to existing ion-imaging methods, especially where resonantly enhanced multiphoton ionization detection of fragments is problematic.